Tensors for Data Processing: Theory, Methods, and Applications - Liu, Yipeng (Elsevier Science & Technology, 2021)
Tensors for Data Processing: Theory, Methods and Applications presents both classical and state-of-the-art methods on tensor computation for data processing, covering computation theories, processing methods, computing and engineering applications, with an emphasis on techniques for data processing.